2020
DOI: 10.1152/japplphysiol.00652.2020
|View full text |Cite
|
Sign up to set email alerts
|

Increased peak end-expiratory pressure in ventilated preterm lambs changes cerebral microvascular perfusion: direct synchrotron microangiography assessment

Abstract: Positive end expiratory pressure (PEEP) improves oxygenation in mechanically ventilated preterm neonates by preventing lung collapse. However, high PEEP may alter cerebral blood flow secondary to the increased intrathoracic pressure, predisposing to brain injury. The precise effects of high PEEP on cerebral haemodynamics in the preterm brain is unknown. We aimed to assess the effect of PEEP on microvessels in the preterm brain using synchrotron radiation (SR) microangiography which, enables in vivo real-time h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…We have previously utilised synchrotron microangiography to investigate cerebral haemodynamics in the preterm newborn lamb which has a brain size comparable to that of the human newborn. 21 The current study has explored and extended the use of synchrotron microangiography in functional brain imaging for the first time and has characterised the functional haemodynamic response based on changes in microvessels in the immature brain. We found that in response to somatosensory stimulation of increasing durations in the 7-10-day old term lambs, more cerebral microvessels were recruited as indicated by vessel contrast transit and visualisation, but there was no overall change in the vessel diameters of the visibly perfused vessels at different durations of stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously utilised synchrotron microangiography to investigate cerebral haemodynamics in the preterm newborn lamb which has a brain size comparable to that of the human newborn. 21 The current study has explored and extended the use of synchrotron microangiography in functional brain imaging for the first time and has characterised the functional haemodynamic response based on changes in microvessels in the immature brain. We found that in response to somatosensory stimulation of increasing durations in the 7-10-day old term lambs, more cerebral microvessels were recruited as indicated by vessel contrast transit and visualisation, but there was no overall change in the vessel diameters of the visibly perfused vessels at different durations of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The ewe was intubated, placed in a prone position and anaesthesia was maintained via inhaled 1-2.5% isoflurane with mechanical ventilation and fractional inspired oxygen to keep peripheral arterial oxygen saturation (SpO 2 ) >95%. Preterm lambs were partially exteriorized via a maternal midline abdominal incision and hysterotomy for fetal instrumentation as described previously, 21 whilst maintaining the placental-umbilical circulation. Briefly, a nonocclusive polyvinyl catheter was inserted into the fetal right carotid artery with the catheter tip at the level of the mandibular angle, before the carotid bifurcation, for administration of iodine contrast agent.…”
Section: Surgery and Lamb Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…(11) The impact of higher PEEP levels at birth is less clear, with a recent pilot lamb study suggesting engorgement of micro-vessels and an increase in CeBF. (12) . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%